Laparoscopic radiofrequency ablation of hepatocellular carcinoma: A critical review from the surgeon's perspective - Santambrogio, R. (Elsevier, 2008)
BACKGROUND: The treatment of choice for hepatocellular carcinoma (HCC) is surgical resection but only a small percentage of patients are operative candidates. Percutaneous radiofrequency interstitial thermal ablation (RFA) has proved to be effective in the treatment of unresectable HCC. However, there is a sub-group of patients who may benefit from a laparoscopic rather than a percutaneous approach. Laparoscopic RFA offers the combined advantages of improved tumor staging based on the intracorporeal ultrasound examination and safer access to liver lesions that are difficult or impossible to treat with a percutaneous approach. The aim of our review was to evaluate the advantages and limitations of the laparoscopic approach, according to the criteria of evidence-based medicine. CONCLUSIONS: Laparoscopic RFA of HCC proved to be a safe and effective technique, at least in terms of the short- and mid-term results. This technique may be indicated in selected cases of HCC when percutaneous RFA is very difficult or contraindicated.